Suicidal Ideation and Skill Use During In-patient Dialectical Behavior Therapy for Borderline Personality Disorder. A Diary Card Study - Probst, Thomas; Decker, Verena; Kießling, Eva; Meyer, Sascha; Bofinger, Christine; Niklewski, Günter; Mühlberger, Andreas; Pieh, Christoph (Frontiers in Psychiatry, 2018)
Associations between suicidal ideation and skill use were investigated during in-patient dialectical behavior therapy (DBT) for borderline personality disorder (BPD). Participants were N=44 patients with BPD undergoing a five-week in-patient DBT program in a psychiatric clinic. They filled in a diary card each treatment day resulting in 1,334 skill use ratings and 1,364 suicidal ideation ratings. Days were categorized into three categories: days with successful skill use (using skills and perceiving them as effective), days without skill use, days with unsuccessful skill use (using skills but perceiving them as ineffective). Multilevel models were performed to account for the nested data structure. The results showed that suicidal ideation improved more for patients who applied skills successfully more often during treatment (p<.05). Moreover, suicidal ideation was lower on treatment days with successful skill use compared to treatment days without skill use and compared to treatment days with unsuccessful skill use (p<.05). When treatment days with no skill use were compared to treatment days with unsuccessful skill use, suicidal ideation was higher on treatment days with unsuccessful skill use (p<.05). To conclude, using skills successfully on as many treatment days as possible is associated with lower suicidal ideation.